Albumin‐Assisted Method Allows Assessment of Release of Hydrophobic Drugs From Nanocarriers. Issue 1 (25th September 2017) - Gil, Dmitry; Frank‐Kamenetskii, Anastasia; Barry, John; Reukov, Vladimir; Xiang, Yun; Das, Arabinda; Varma, Abhay K.; Kindy, Mark S.; Banik, Naren L.; Vertegel, Alexey
Abstract : Polymeric nanoparticles have been extensively studied as drug delivery vehicles both in vitro and in vivo for the last two decades. In vitro methods to assess drug release profiles usually utilize degradation of nanoparticles in aqueous medium, followed by the measurement of the concentration of the released drug. This method, however, is difficult to use for drugs that are poorly water soluble. In this study, a protocol for measuring drug release kinetic using albumin solution as the medium is described. Albumin is a major blood transport protein, which mediates transport of many lipid soluble compounds including fatty acids, hormones, and bilirubin. The use of a dialysis‐based system utilizing albumin dialysate solution allows hydrophobic drug release from a diverse set of drug delivery modalities is demonstrated. The method using liposomes and PLGA nanoparticles as drug carriers, and two model hydrophobic drugs, 17β‐estradiol, and dexamethasone is validated. Abstract : Nanomedicine is a powerful treatment modality that is extensively tested in various areas of biomedical engineering. However, the translation of the research into clinical practice is slow, due to due to improper assessment of drug release kinetics in vitro. This study describes novel biotechnological method for assaying drug release kinetics from nanomedicines. This work aims to help scientists to accurately evaluate the performance of novel drug delivery systems prior to conducting comprehensive animal studies.